(untitled) (Comprehensive Journal of Science, 2025)
This study aims to examine internal auditing standards and their impact on the effectiveness of internal control systems within Libyan commercial banks. To achieve its objectives, the study employed a descriptive-analytical methodology to assess the perceptions of the study sample, which consisted of 44 employees. Following the distribution of the questionnaire, 40 valid responses were retrieved and subsequently analyzed using SPSS. The overall findings indicate that internal auditing standards exert a significant influence on the effectiveness of internal control systems. The study concludes with several recommendations and proposed solutions, the most notable of which are: increasing the human and technical resources allocated to internal audit departments to enhance their operational effectiveness, and strengthening cooperation between internal audit and compliance departments to ensure adherence to both internal and external regulatory frameworks.